Financial Report Application Design: Case Study at Perhutani Tambak Ruyung East Pasir Jambu - Rima Melati; Alia Tri Utami; Asep Sudrajat; Cahyo Hermanto; Aris Dianto (LPPM STMIK Mardira Indonesia, 2023)
Currently, PERUM Perhutani Tambak Ruyung Timur continues to rely on manual methods for financial reporting, resulting in incomplete financial reports. The process above has the potential to be significantly unproductive and inefficient, hence increasing the likelihood of errors in the recording procedure. Based on the backdrop above, PERUM Perhutani Tambak Ruyung Timur must implement a more pragmatic financial accounting recording system. Hence, the author interned at the organization above and produced a comprehensive Internship Report entitled